2013
DOI: 10.1111/jawr.12091
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Decade Watershed Approach to Stream Restoration Log Jam Design and Stream Recovery Monitoring: Finney Creek, Washington

Abstract: A federal, state, and private partnership leveraged resources and employed a long-term, systematic approach to improve aquatic habitat degraded by decades of intensive forest management in Finney Creek, a tributary to the Skagit River of Northwest Washington State. After more than a decade of work to reduce sediment sources and the risk of landslides within the watershed, log jam installation commenced in 1999 and progressed downstream through 2010. Log jam design was adapted as experience was gained. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…), and increasing channel roughness to encourage more water exchange between the channel and cooler hyporheic flows (Arrigoni et al. ; Nichols and Ketcheson ). More aggressive measures have also been discussed, such as excavating deep pools adjacent to warm rivers to access cool groundwater or the construction of wingwalls upstream of cold tributary inflows to limit mixing and create microrefugia (Kurylyk et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and increasing channel roughness to encourage more water exchange between the channel and cooler hyporheic flows (Arrigoni et al. ; Nichols and Ketcheson ). More aggressive measures have also been discussed, such as excavating deep pools adjacent to warm rivers to access cool groundwater or the construction of wingwalls upstream of cold tributary inflows to limit mixing and create microrefugia (Kurylyk et al.…”
Section: Discussionmentioning
confidence: 99%
“…Options exist to ameliorate thermal stresses on salmon and trout populations, but appropriate remedies are context dependent and will require strategic prioritization (Beechie et al 2013;Orr et al 2015). Restoration efforts to cool rivers might include minimization of flow diversions (Elmore et al 2015), increasing shade provided by riparian vegetation (Cristea and Burges 2010;Johnson SALMON AND TROUT RIVER WARMING and Wilby 2015), reconnecting rivers to floodplains to enhance habitat diversity (Beechie et al 2013), and increasing channel roughness to encourage more water exchange between the channel and cooler hyporheic flows (Arrigoni et al 2008;Nichols and Ketcheson 2013). More aggressive measures have also been discussed, such as excavating deep pools adjacent to warm rivers to access cool groundwater or the construction of wingwalls upstream of cold tributary inflows to limit mixing and create microrefugia (Kurylyk et al 2015).…”
Section: Adaptive Responsesmentioning
confidence: 99%
“…2). These include placing logs and whole trees with heavy equipment or helicopter or felling nearby trees into a stream and letting the channel do much of the work distributing the wood (Carah et al 2014;Nichols and Ketcheson 2013). That being said, fixed wood structures or limiting the mobility of wood have become commonplace in larger managed streams (>20 m bankfull width) where liability, engineering, and human safety concerns dominate project design objectives (Abbe et al 2002) or in newly constructed channels where vegetation is not yet established and bank erosion concerns are high.…”
Section: Stability Of Placed Woodmentioning
confidence: 99%
“…Climate change will presumably alter upland hydrological processes that drive water-temperature regimes, thus increasing understanding of how water-temperature regimes affect aquatic ecosystems has become increasingly important (McCullough et al, 2009;Olden & Naiman, 2010;Ruesch et al, 2012). Changing water-temperature regimes will presumably have deleterious effects on some species or life stages of stream-rearing anadromous salmonids (Battin et al, 2007), a presumption that has in part driven efforts to restore historical temperature regimes and improve in-stream refuge (Nichols & Ketcheson, 2013). The present analytical approach confirmed that water-temperature monitoring will continue to be useful for diagnosing which factors limit growth of rearing salmonids and how those factors could be addressed (Beer & Anderson, 2011;Wenger et al, 2011).…”
Section: Discussionmentioning
confidence: 99%